LAYANAN KONSELING KELOMPOK MELALUI KEGIATAN EKSTRAKURIKULER DALAM MENANGANI TAWURAN SISWA - Merdekawati (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This research is motivated by the recurrence of brawl behavior between schools in MTs Negeri 1 Purwakarta. The research objective was to increase the positive attitude of students who were involved in brawls with group counseling services through extracurricular activities. The research subjects were grade VIII students in the odd semester of the 2014-2015 academic year which consisted of several classes that were involved in brawls. The research procedure consists of several stages, namely: 1) preparation in the form of collecting student initial data, determining the majority class that has problems, preparing an initial screening questionnaire and its application, identifying problems, grouping students, determining extracurricular activities and planning actions. 2) the implementation of the research which consists of three cycles. Each cycle consists of planning, acting, observing, and reflecting. The results showed that during the counseling process fellow students supported and encouraged each other to face problems. At each cycle the results of filling out the development sheet and attitude showed an increase. In cycle I students who answered agreed the average was less than 50%, in cycle II students who answered agreed increased the average to 60%, and in cycle III more than 70% of students who answered agreed. The results of the evaluation of group counseling services showed that an average of 80% of students could time the extracurricular activities they participated in, this means that extracurricular activities that students participated in could change attitudes and behavior to be good.